PENERAPAN MODEL LEARNING CYCLE 5E UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS PESERTADIDIK DALAM MATERI TRIGONOMETRI - Ayuni Ayuni; Yulis Jamiah; Ahmad Yani T (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe purpose of this study was to describe the implementation of learning cycle 5e (engagement, exploration, explanation, elaboration, and evaluation) to improving students mathematic communication skills in trigonometry material. The form of this study used experimental method with a design which was one group pretest-posttest. The population consisted of all students 1st grade at SMA Santo Fransiskus Asisi Pontianak. According to the purposive sampling technique, the X MIPA class was then chosen as a sample. The data of this study collected by mathematic communication skills test and observation sheet. There was several points resulting from this study, such as (1)The average of the students mathematic communication skills test result which before and after the implementation of learning cycle 5e was 5,55 and 8,45 respecively; (2) The t-test result showed that students mathematic communication skill between before and after the implementation of learning cycle 5e have a difference. This difference was show by n-gain that is on fair levels. In general, the conclution of this study was implementation of learning cycle 5e is good to used to increased students mathematic communication skills, especially in trigonometry material at X MIPA SMA Santo Fransiskus Asisi Pontianak.Keywords: Learning Cycle 5E, Mathematic Communication Skills, Trigonometry Material